SISTEM PENGONTROLAN DAN MONITORING PADA KANDANG AYAM BROILER BERBASIS INTERNET OF THINGS (IOT) - Hendrikus Hendrikus; Fatma Agus Setyanigsih; Suhardi Suhardi (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2022)
Broilers are chickens that are widely kept by breeders for the purpose of meat production because they have a very fast growth rate and can be harvested at the age of 6-7 weeks. The process of maintaining conventional broiler chickens still uses a manual feeding system, water and temperature that are not controlled so that it requires a lot of time in maintenance. Therefore, we need a system that can monitor and control the temperature, humidity, water level, lights and feed according to the needs in the broiler chicken coop without having to come to the cage directly. In this study, a website system was used to monitor and control IOT-based broiler chicken coops. uses 2 NodeMCU ESP32 and NodeMCU ESP8266 to control all hardware and software components. The DHT11 sensor reads the temperature and humidity of the air, the first ultrasonic sensor to read the water level and the second ultrasonic sensor to read the height and remaining feed. Observation of the development of broiler chickens was carried out by comparing data on internet-based broiler chicken cages and conventional cages during a two-week maintenance period with a total of five broiler chickens in each cage. The results of the observational test on weight growth of broiler chickens in cages based on the internet of things weigh an average of 417 grams and in conventional cages the average weight is 278.8 grams.